Meaningful and Memorable Learning: Integrating TPR and Youtube Videos to teach Vocabulary - Istiqlaliah Nurul Hidayati (International Journal of Quantitative Research and Modeling, 2020)
The teaching of vocabulary is very essential in teaching a particular language. In Indonesia, English is taught from kindergarten up to higher educations. Unfortunately not all of the teachers in those levels especially in kindergartens and primary schools major in English or at least have good English proficiency. That is why English Language Education Study Program, the Faculty of Teacher Trainings and Educational Sciences, Pakuan University always conducts community service to provide trainings to teachers from any part of the city. The first thing done before the community service was doing need analysis. In 2019, the result of the need analysis was the teaching of vocabulary which is fun and meaningful. 28 teachers were involved in this research. They were divided into two groups to conduct experiment. From the experiment, it is proven that the training given to the teachers increase their understanding about TPR and the teaching of vocabulary. The teachers were also given questionnaire to find out their perception on the use of TPR and YouTube and from the questionnaire the teachers think that  their knowledge on the teaching using TPR increased their knowledge and they can find benefits in using TPR and YouTube in the classroom namely: the use of TPR itself can help them accommodate students’ different learning styles, teach vocabulary in context so that it is more meaningful, and the teaching learning situation becomes more fun.